Numerical investigation of transient hydration of unsaturated geosynthetic clay liners. Issue 3 (June 2012) - Siemens, G.; Take, W.A.; Rowe, R.K.; Brachman, R.W.I.
Abstract : ABSTRACT: Geosynthetic clay liners (GCLs) are commonly used as hydraulic barriers, owing to their low hydraulic conductivity and their ability to form a composite barrier system with geomembranes. The GCL is manufactured and placed at a low initial moisture content, and must hydrate in the field in order to function as an effective barrier. With the overlying geomembrane limiting infiltration from above, moisture must come from the underlying foundation soil. In this paper, numerical simulations are completed to calibrate models for GCL hydration followed by a sensitivity analysis on the underlying soil properties and moisture content. The results show that the driving factor used to predict the GCL hydration level is the suction value provided by the underlying soil. The GCL requires such a small quantity of moisture relative to the amount in the soil that the suction within the soil at the beginning and end of models is relatively constant. The time rate of GCL hydration was found to be mainly a function of the unsaturated properties of the GCL. A methodology is developed to predict the final GCL moisture content and time rate of hydration.